Pemanfaatan Limbah Rumah Tangga Minyak Jelantah Dengan Ekstrak Jeruk Dalam Perspektif Komunikasi Lingkungan Di Kelurahan Kaligandu - Siska Mardiana; Rahmi Mulyasih; Rama Tamara; Ahmad Sururi (Jurnal SOLMA, 2020)
Kaligandu Village is one of the villages located in the District of Serang, Serang City. The use of waste cooking oil household waste repeatedly by the community and the environment, especially those who have culinary businesses, encourage innovation in the utilization of waste cooking oil household waste with orange extract in the perspective of environmental communication. This Community Service activity includes 4 (four) stages, namely material, energy, information and evaluation. The results of these community service activities can have an impact as expected. The entire PkM program is running 100%, there is a public understanding of the importance of maintaining environmental cleanliness and an increase in community understanding about the use of waste cooking oil household waste with citrus extracts that have economic value.